E-Health Applications and Data Protection: a comparison of selected European Union members’ national legal systems - Ferreira, Tatiana (Bioethica, 2022)
In a context of constant evolutions and digitalization of the world, the health industry is one of the most relevant areas of innovation, especially with the development of countless types of electronic health (e-health) applications such as electronic health records or health applications on mobile devices. Furthermore, as data is becoming increasingly valuable, patients’ health data, in particular, require the highest level of attention as it is vastly confidential and stored in massive amounts in e-health applications. Along with the development of new technologies, law is deemed to follow for regulating it. This implies that law must act as a protector for health data. Within the European Union, the issue of data protection has been dealt with by the European Commission notably through the General Data Protection Act (GDPR) in 2018, but it is each country’s responsibility to deal with new technologies in health, implement and apply data protection to health data. Thus, it is relevant to compare how European countries deal with health data managing issues in e-health applications from a legal perspective and evaluate how efficient they are. For the purpose of this research, only three types of health applications will be compared as a sample, including electronic health records, electronic prescriptions and mobile health applications.